Residential energy demand elasticity in Ghana: an application of the quadratic almost ideal demand systems (QUAIDS) model - Divine Kwaku Kutortse (Cogent Economics & Finance, 2022)
The paper seeks to analyze residential energy use patterns and the price and energy expenditure responsiveness of household demand for residential energy in Ghana, using GLSS 7 data, the multivariate probit model, and the Quadratic Almost Ideal Demand System (QUAIDS) model. The study focuses on four main fuels; firewood, charcoal, and others (FCO), LPG, electricity, and kerosene. The results show that the demand for all household energy fuels in Ghana was significantly influenced by price, income, and social demographic factors. Household demand for electricity and LPG fuels are income elastic with values greater than 1, while FCO and kerosene fuels are income inelastic. The own-price elasticity also shows modern fuel (LPG and electricity) as the most responsive fuel to a price increase, even though all energy fuels are price inelastic and negative. The complementary cross-price elasticity of all fuels estimated must be carefully interpreted in the context of the cultural factors, socioeconomic factors, and the unique purposes of each fuel. After a robustness check was done in correcting for bias arising from zero energy expenditure, the study finds that the own-price elasticity for modern energy fuel (LGP and ECG) reduced slightly, even though the demand for all energy fuel remains negative and price inelastic. The study includes implications for policies geared towards reducing the price of residential energy fuels and policies to ensure clean and efficient residential energy fuels are readily accessible for consumption.
Keywords: 330; residential energy; demand elasticity; quadratic almost ideal demand system; Ghana; household